2010
DOI: 10.1017/s1368980010000765
|View full text |Cite
|
Sign up to set email alerts
|

Breakfast skipping and its relation to BMI and health-compromising behaviours among Greek adolescents

Abstract: Objective: The increasing prevalence of obesity worldwide is a major health concern. Our study, which is part of the First National Epidemiological Study of Obesity in Greece, aimed to assess (i) breakfast habits and their relationship to BMI in Greek adolescents, as well as (ii) breakfast skipping in relation to other health behaviours. Design: Epidemiological survey throughout Greece. Participants completed a questionnaire concerning breakfast habits and many lifestyle parameters. Setting: The survey was con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
45
2
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(59 citation statements)
references
References 24 publications
(43 reference statements)
9
45
2
3
Order By: Relevance
“…In our study, we did not find significant differences in the frequency of daily breakfast consumption between boys and girls. In the current study, older adolescents were found to consume breakfast irregularly more often, compared to those who are younger, which was consistent with previous studies [11,16,20]. The age disadvantage of older adolescents in breakfast consumption could be explained by the decreased parental influence, greater concerns about their body image and time considerations [16,23].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In our study, we did not find significant differences in the frequency of daily breakfast consumption between boys and girls. In the current study, older adolescents were found to consume breakfast irregularly more often, compared to those who are younger, which was consistent with previous studies [11,16,20]. The age disadvantage of older adolescents in breakfast consumption could be explained by the decreased parental influence, greater concerns about their body image and time considerations [16,23].…”
Section: Discussionsupporting
confidence: 91%
“…To formulate comprehensive health promotion strategies, a number of studies have explored the interrelations between multiple health-related behaviors, which involve dietary patterns, as well as smoking cigarettes, drinking alcohol, and physical activity [15,16,17,18]. Recently, the associations between breakfast consumption and a clustering of health-related behaviors have received more attention from public health professionals.…”
Section: Introductionmentioning
confidence: 99%
“…However, this relationship did trend toward significance, which may warrant further research. Relationships between BMI and breakfast consumption have not been well established in the literature (Abalkhail and Shawky 2002; Boutelle et al 2002; Kapantais et al 2011; Lawman et al 2014; Nuru and Mamang 2015; Ostachowska-Gasior et al 2016; Resnicow 1991; Siega-Riz, Popkin, and Carson 1998; Sjöberg et al 2003; Walker et al 1982; Wolfe et al 1994). In a recent publication assessing myths, presumptions, and facts about obesity, Casazza et al (2013) delved into the presumption that breakfast consumption protects against obesity and found there was no difference in weight among those assigned to skip breakfast versus those assigned to eat breakfast (Astbury, Taylor, and Macdonald 2011; Casazza et al 2013; Farshchi, Taylor, and Macdonald 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, this study evidenced an association between the habit of skipping breakfast with obesity and a higher total calorie intake, which can be understood as a metabolism compensation [38,43], as the individual eats more calories during the day to compensate the lack of breakfast [9,44]. This process may facilitate the intake of excessive calories, which was observed in this study and corroborated by previous studies [12,18] providing evidence that skipping breakfast is not an effective way to manage weight [45].…”
Section: Discussionmentioning
confidence: 99%
“…The epigenetic factors also play an important role in the development of obesity, especially because the main characteristic that triggers the fat accumulation is the imbalance between energy intake and energy expenditure [7]. The energy imbalance that have been associated with the genesis of obesity may be explained by the recent changes observed in the population's dietary patterns, which includes an increasing intake of energy-dense food products, caloric beverages (such as soft drinks) and processed food products, besides the diminished frequency of physical activity observed nowadays [8,9]. …”
Section: Introductionmentioning
confidence: 99%